UI design of buying and selling application and renting items at Telkom University Campus through the user-centered design method - Arya Safa Maulana; Dadang Setiawan; Dana Sulistiyo Kusumo (Jurnal Mantik, 2023)
Online buying and selling activities and renting goods are familiar to young people or college students. For instance, the Telkom University campus has a buying and selling forum (FJB Telkom) using Line social media platform as a buying and selling activity. However, Line social media primarily known as an instant messaging application, and as a result, the researchers conducted a survey among Telkom University students related to buying and selling activities on FJB Telkom and renting activities around campus. Based on the results of 105 respondents, it was found that 69,5% stated that FJB Telkom using the Line platform could have been more efficient due to the lack of feature needs for buying and selling activities. Therefore, this study aims to design a user interface (UI) design for the FJB Telkom application by adding rental features that can assist Telkom University students in buying, selling, and renting items activities around campus. UI design was conducted with the User Centered Design (UCD) method approach that focused on the characteristics of user needs. The UCD method included a testing stage or usability testing. The user interface of the FJB Telkom application was tested using prototype testing and the System Usability Scale (SUS). The test results obtained from respondents indicated that the UI design of the FJB Telkom application achieved an average SUS score of 85,5% and received an excellent grade on the SUS score. Thus, the user interface of the FJB Telkom application successfully build a system with high usability.